Digital Teaching, Material Need Students Write Information on Fiction and Nonfiction Book Based on Critical Literacy in Junior High School - Sumirah Sumirah; Ida Zulaeha; Hari Bakti Mardikantoro; Haryadi Haryadi (Universitas Negeri Semarang, 2023)
Critical literacy in learning to write information crucial awareness growth for students to find important information based on the terms contained in the text. Facts on the ground show that learning to report information on fiction and nonfiction books has not yet reached a critical level. Therefore, on this occasion, the research aims to determine the need for digital teaching materials for writing information on fiction and nonfiction books based on critical literacy. This study used 30 students as a sample. The method used in this research is the descriptive qualitative method. Based on the results of research conducted at SMP Negeri 1 Kesugihan, get the fact that during this need for digital teaching materials, writing information on fiction and nonfiction books based on critical literacy is a solution to the lack of digital teaching materials for reporting information on fiction and nonfiction books at Kesugihan 1 Middle School. This research has implications for improving the potential shortage of teaching materials by realizing the importance of technology for education, especially writing material for critical fiction and nonfiction books.